Osteoporosis and its complications: treatment adherence and possibilities of its enhancement - O V Dobrovol'skaya; O A Nikitinskaya; Nataliya Vladimirovna Toroptsova; O. V. Dobrovolskaya; O A Nikitinskaya; Nataliya Vladimirovna Toroptsova (Современная ревматология, 2011)
Objective. To estimate patient adherence to treatment with antiosteoporotic drugs within the first year after experienced low-trauma osteoporotic fractures (LOF). Material and methods. The data of a questionnaire survey were analyzed in 172 women aged 50 years or older (mean age 66+8 years) who had sustained fractures at different sites after a fall from standing height, were analyzed. Therapy and its compliance were assessed 12 months after LOF. Results and discussion. Among the 172 respondents, 55% received therapy, including 73% took only calcium preparations and vitamin D; 8% calcitonin; 14% bisphosphonates; 5% strontium ranelate. At the same time, 45% of those asked were given no antiosteoporotic drugs within the first year of life after fracture. Only 42%> continued to receive treatment following 12 months; 18% interrupted it within the first 4 months after fracture. Conclusion. In real clinical practice, osteoporosis was not treated in the majority of patients within the first year after LOF. One of the major reasons why it is not treated is the high cost of pathogenetic drugs. This reason can be successfully eliminated using generic drugs.